High temperature stability of Ba0.5Sr0.5Co0.8Fe0.2O3−δ and La0.6Sr0.4Co1−yFeyO3−δ oxygen separation perovskite membranes. Issue 7 (June 2016) - Brisotto, Mariangela; Cernuschi, Federico; Drago, Francesca; Lenardi, Cristina; Rosa, Patrizia; Meneghini, Carlo; Merlini, Marco; Rinaldi, Claudia
Abstract: The Barium (BSCF) and Lanthanum (LSCF) strontium cobalt–ferrite, are among the most studied mixed ionic electronic conducting materials having interesting properties as Oxygen Transport Membranes. In this paper the two materials are analysed after long term aging at high temperatures and permeation tests. Several characterisation techniques are used to understand degradation mechanisms. Surface layers were analysed by X-ray photoelectron spectroscopy: LSCF is stable, while on BSCF a thin layer of carbonates forms. Quantitative synchrotron radiation diffraction measurements of hexagonal phase content in aged BSCF allows determining Avrami coefficients at 780, 800 and 820 °C. This process is associated to the enrichment of Fe in the regions of grains near the lamellar hexagonal phase, as WDS maps show. Bulk measurements of X-ray Absorption Near Edge Structure (XANES) and the analysis of the Co2p doublet in XPS spectra confirm a reduction of Co ions oxidation number after long time at intermediate temperatures.